Natalizumab for the treatment of relapsing multiple sclerosis - Richard A Rudick (Dove Medical Press, 2008)
Richard A Rudick1, Michael A Panzara21Cleveland Clinic Foundation, Cleveland, OH, USA; 2Biogen Idec, Inc., Cambridge, MA, USAAbstract: Natalizumab is an α4-integrin antagonist approved as monotherapy for patients with relapsing multiple sclerosis (MS), based on demonstrated efficacy in the pivotal AFFIRM study (N = 942). Natalizumab monotherapy reduced risk of disability progression by 42%–54% and annualized relapse rate by 68% during a period of 2 years. Natalizumab was also associated with significant reductions in number of T2-hyperintense, gadolinium-enhancing, and T1-hypointense lesions and in volume of T2-hyperintense lesions (all p < 0.001) on magnetic resonance imaging. Furthermore, natalizumab-treated patients in AFFIRM experienced significant improvements from baseline in the physical and mental components of the Short Form-36 (p ≤ 0.01) and a 35% reduction in risk of clinically significant vision loss (p = 0.008 vs placebo). Natalizumab was well tolerated in phase 3 studies. Common adverse events were generally mild and included headache, fatigue, urinary tract infections, and arthralgia. Serious adverse events were similar between treatment groups. The incidence of serious hypersensitivity reactions associated with natalizumab was <1%. Progressive multifocal leukoencephalopathy was a rare complication of treatment, observed in 2 patients with MS who received natalizumab plus interferon β-1a. The robust clinical benefits of natalizumab, including benefits on patient-reported quality of life, make it an important addition to disease-modifying therapies available to patients with relapsing MS.Keywords: multiple sclerosis, natalizumab, α4-integrin antagonist